Influence of heat-transfer resistances in an optimized multifunctional reactor. (12th October 2022) - Behloul, Chakib R.; Smahi, Abdelhadi; Commenge, Jean-Marc; Castel, Christophe
Highlights: Effect of heat-transfer resistances on intensified reactor design. Optimal design of a multifunctional reactor. Solving optimization problems using genetic algorithm. Optimal management of heat exchange and water separation. Significant performance enhancement due to high synergy between elementary functions. Abstract: This work presents a detailed model for the implementation of the dimethyl ether (DME) direct synthesis from CO2 and H2 in an intensified equipment. The effect of heat-transfer resistances within a multifunctional reactor is studied. Considering these resistances has demonstrated their influence on the temperature profile, hence, their role for both catalyst activity and membrane stability: a higher hot spot of about 20 °C is obtained within the first reactor segments. Based on a proper methodology, optimization approaches are proposed for the optimal heat management and water separation. Considering these heat-transfer resistances influences the optimal heat flux and water separation profiles, thus the optimized reactor design. Up to 80% in DME yield per single pass can be achieved proving the synergy between functions for process improvement. Simulation results demonstrate the strong DME yield dependence on the extracted water profile as well as on the heat flux profile exchanged with the coolant.